ANALYSIS OF THE ACCURACY OF THE DIAGNOSIS CODE AND METHODS BEFORE AND AFTER VERIFICATION ON THE MEDICAL RECORDS OF BPJS PATIENTS IN RSUD dr. SOEDIRAN MANGUN SUMARSO - Dian Sulastri (Indonesian Journal of Health Information Management, 2024)
Cases of pending BPJS Health claims are still a problem, as many as 9.7% (79) of medical records. This study aims to analyze differences in the accuracy of diagnosis codes and procedures before and after verification in the medical records of BPJS patients at dr. Soediran Mangun Sumarso. This type of research is comparative analysis. A population of 806 medical records with a sample size of 261 was taken through random sampling technique. Method of collecting data through observation and unstructured interviews. Data analysis using the chi square test. The results of the study showed that there was a significant difference between the accuracy of the diagnosis code and the procedures before and after verification at dr. Soediran Mangun Sumarso.